1974
DOI: 10.1063/1.1681432
|View full text |Cite
|
Sign up to set email alerts
|

Equations of motion method: Excitation energies and intensities in formaldehyde

Abstract: We have used the equations of motion method to study the excitation energies and intensities of electronic transitions in formaldehyde. The calculated excitation energies and oscillator strengths agree well with experiment and suggest explanations for some unusual features recently observed in the optical absorption and electron scattering spectrum of formaldehyde in the vacuum ultraviolet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
2

Year Published

1974
1974
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(13 citation statements)
references
References 13 publications
3
8
0
2
Order By: Relevance
“…This observation is shared by previously reported theoretical data [5,8,11,12]. Whereas the EOM-based data [11,12] for these three states are in acceptable agreement with our MR-CISD and MR-AQCC/LRT oscillater strengths, the MR-DCI [8] and the generalized valence bond CI [5] method predict weaker transition intensities, especially for the n±3s excitation. On the other hand, the reported oscillator strengths for the n±3d excitations from EOM calculations [12] are by up to 4 times larger than those derived from CI methods.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This observation is shared by previously reported theoretical data [5,8,11,12]. Whereas the EOM-based data [11,12] for these three states are in acceptable agreement with our MR-CISD and MR-AQCC/LRT oscillater strengths, the MR-DCI [8] and the generalized valence bond CI [5] method predict weaker transition intensities, especially for the n±3s excitation. On the other hand, the reported oscillator strengths for the n±3d excitations from EOM calculations [12] are by up to 4 times larger than those derived from CI methods.…”
Section: Resultssupporting
confidence: 82%
“…Such comparisons have to be regarded sometimes with caution since computed vertical excitation energies do not have a directly observable experimental counterpart. We recon®rm the ®nding that the vertically excited n±3p z state is lower in energy than the n±3p y state, a fact ®rst observed by Yeager and McKoy [11] and Harding and Goddard [5] and reemphasized by Hachey et al [6]. At the MR-CISD and MR-CISD+Q levels using the MINVAL reference space and the [431/ 21] basis set, the energetic splitting of these two states is rather small ( Table 3).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The present calculated first electronic excitation energy is 4.44 eV which finds excellent agreement with the theoretical data of Kaur and Baluja [22] and in Refs. [20,21,[25][26][27]. The rotational constant obtained in the present calculation is 9.406 cm −1 and is also in excellent agreement with experimental and theoretical data from the National Institute of Standards and Technology (NIST) [24] .…”
Section: A Target Modelsupporting
confidence: 86%
“…Since 1970, several theoretical calculations have been performed to predict the accurate location and assignment of various valence and Rydberg states. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Most of these calculations, which focus on different aspects such as geometrical structure, vertical and adiabatic excitation energies, and frequencies of excited states, have been reviewed by Jose et al [39] It may be seen from literature that the only strong valence transition observed is from the ground state to the first excited singlet state in 4.08 eV region assigned to the à 1 A 2 ÀX 1 A 1 band system and that it consists of an extended progression of vibronic bands. [8,21] Some of the Rydberg states are well located, but there is ambiguity in respect of the vertical ordering of some low-lying Rydberg transitions, viz 1 B 2 (n-3p z ), 1 A 1 (n-3p y ), and the absence or weak structures of other excited valence states, viz 1 A 1 (p À p à ), 1 B 1 (r À p à ), that are expected to lie in the same energy region.…”
Section: Introductionmentioning
confidence: 99%